Roles of religious actors in the West African Ebola response. Issue 5 (4th July 2017) - Marshall, Katherine
ABSTRACT: More than 11, 000 people died during the 2014–15 Ebola epidemic. It devastated the communities concerned and set back progress in building health systems and socio-economic development more broadly. Concentrated in three poor West African countries, Guinea, Liberia, and Sierra Leone, the tremors reverberated worldwide, spurring mobilisation of vast human and financial resources. The epidemic highlighted contemporary challenges for public health, particularly in fragile states, with lessons extending far beyond health sectors. Religious actors played distinctive roles at various points and across different sectors. This article focuses on religious responses to the 2014 Ebola epidemic and implications for public health practitioners.